Indonesian Patent Law Reform for Simple Patent Innovations on Achieving Welfare State Objectives - Waspiah Waspiah; Budi Santoso; Paramita Prananingtyas; Muhammad Iqbal Baiquni; Dany Eka Saputra (Journal of Indonesian Legal Studies, 2023)
The main focus of this research is to examine the legal protection of simple patent innovations within the Indonesian patent system, considering their substance, structure, and legal culture. The objective is to advocate for the reformulation of regulations concerning the social and economic utilization of intellectual property, specifically simple patents, in order to address their impact on public interest from a welfare state perspective. The current regulations governing simple patents demonstrate monopolistic and individualistic tendencies. This study utilizes a normative juridical research method and employs a statute-based approach to critically analyze the provisions of Law No. 13 of 2016, commonly known as the Patent Law. The research findings indicate that the current regulation fails to adequately support inventors of simple patents. The existing first-to-file registration system, resembling that of regular patents, has resulted in low rates of acquisition and registration for simple patents. Consequently, it can be concluded that the regulation of simple patents under the Patent Law does not favor inventors of such patents. In order to rectify this issue, it is crucial to reformulate the legal protection of simple patent innovations based on the principles of the welfare state. The ideal formulation of the Patent Law should take into account the norms and values prevalent within the inventor community, thereby necessitating a reformulation of the legal protection system rooted in the substance, structure, and legal culture in Indonesia.